Immediate tooth replantation: root canal filling for delayed initiation of endodontic treatment - Daniela Atili Brandini; Marina Fuzette Amaral; Caio Vinícius Lourenço Debortoli; Sônia Regina Panzarini (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study is to evaluate the action of paramonochlorophenol associated with Furacin followed by calcium hydroxide (CH) dressing in the control of inflammatory root resorption in cases of immediate tooth replantation with delayed endodontic treatment. A total of 28 incisors of 3 male dogs were extracted and replanted after 15 minutes, and randomly divided into 3 groups: Group I (n = 8) - endodontic treatment was performed before the extraction and replantation; Group II (n = 10) - endodontic treatment was performed 30 days after replantation and the root canal was filled with CH dressing; Group III (n = 10) - endodontic treatment was performed 30 days after replantation and root canals received temporary medication of paramonochlorophenol-Furacin followed by CH dressing. The animals were euthanized 90 days after replantation. The histomorphological events analyzed at the epithelial reattachment site were the intensity and extent of acute and chronic inflammatory processes, periodontal ligament (PDL) organization, the intensity and extent of acute and chronic inflammatory processes in the PDL space, root resorption, bone tissue, and ankylosis. Data were submitted to the Wilcoxon Signed Ranks Test for group comparison (α = 5%). In Groups I, II and III the periodontal ligament was regenerated and most of the resorption areas were repaired by newly formed cementum. The depth and extent of root resorption were significantly higher in Group II than in Group III. The use of paramonochlorophenol-furacin followed by CH dressing was more effective in controlling inflammatory root resorption after immediate tooth replantation.